(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this Search is to study the relationship between performance management system and the employee performance in Tishreen University, by studying the impact of the performance management system and it various dimensions (performance planning & Goal setting, competencies framework, appraisal results, Information technology, ongoing feedback, distinguishing between high and poor performers for Workers, Rewards and incentives) on employee performance. To develop management practices and improve the performance of individuals, and improvement the university performance. To achieve this, a descriptive analytical approach was adopted in the practical in the search. A questionnaire was designed and distributed Tishreen University employees. A soft sample was selected, 150 members of the research community out. 120 members valid to analysis, The SPSS 19 program was adopted. The study concluded a set of results, there are significant relationships between performance management system and the employee performance of the dimensions of performance management system (performance planning & Goal setting, competencies framework, appraisal results, Information technology, ongoing feedback , distinguishing between high and poor performers for Workers, Rewards and incentives) and employee performance in Tishreen University. The study ended with a set of recommendations, the most important of which is to define a career path for the employee and provide opportunities for career development based on the results of the performance management process, and identify the training and development needs of the employees based on the results of the performance management process.